Design of a Textile Antenna Using Metasurface Technology for Wireless Body Area Networks - Sirait, Nurafifah; Fathurahman, Firhan; Alaydrus, Mudrik; Umaisaroh, Umaisaroh (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2024)
Recently, continuous development and distinctive growth have been observed in implementing wearable sensors and flexible devices in real life. This paper shows a wearable textile antenna design based on a metasurface. It operates in the 3.5 GHz. A proposed model provides light on the metasurface's operation. The prototype of the textile antenna using taslan material was observed and exhibited a relative permittivity of 1.41. Based on these values, we designed a square antenna with an amount of parasitic square around modeled as a planar array. We observed the measured reflection coefficient of the three conditions and saw similar results of the reflection coefficient, which is around -25 dB at 3.5 GHz frequency, and the radiation diagram of the antennas reproduced the simulated one.